2022
DOI: 10.1108/jfmm-05-2021-0111
|View full text |Cite
|
Sign up to set email alerts
|

Fashion entrepreneurial self-efficacy: development and validation of a domain-specific scale

Abstract: PurposeThe purpose of this research is to develop a multidimensional measurement of fashion domain entrepreneurial self-efficacy (FDESE) based on which fashion entrepreneurs will be able to better develop strategies to gain and sustain success in their business development. The research is crucial to advocate fashion entrepreneurship and will provide direction for fashion business incubation services.Design/methodology/approachThis research included three stages with mixed qualitative and quantitative approach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 48 publications
(106 reference statements)
2
0
0
Order By: Relevance
“…This means, the higher the financial support, which is indicated by the ease of access to capital sources, starting a business with their own savings, a good opportunity if you have business capital, the perception of seeking capital as a good idea, always seeking financial support, and feeling that you have an investment, then it is not able to increase the self-efficacy of entrepreneurial students in Bali. The results of this study at the same time strengthen the results of previous research regarding financial support being able to increase entrepreneurial self-efficacy (Khaw et al, 2021;Lang & Liu, 2022;Shi et al, 2020;Sidratulmunthah et al, 2018). It can be concluded that financial support has a positive and significant influence on self-efficacy, this means that the higher the financial support possessed by students, the higher their self-efficacy as entrepreneurs.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…This means, the higher the financial support, which is indicated by the ease of access to capital sources, starting a business with their own savings, a good opportunity if you have business capital, the perception of seeking capital as a good idea, always seeking financial support, and feeling that you have an investment, then it is not able to increase the self-efficacy of entrepreneurial students in Bali. The results of this study at the same time strengthen the results of previous research regarding financial support being able to increase entrepreneurial self-efficacy (Khaw et al, 2021;Lang & Liu, 2022;Shi et al, 2020;Sidratulmunthah et al, 2018). It can be concluded that financial support has a positive and significant influence on self-efficacy, this means that the higher the financial support possessed by students, the higher their self-efficacy as entrepreneurs.…”
Section: Discussionsupporting
confidence: 86%
“…Similarly, the availability of substantial financial support boosts student entrepreneurial self-efficacy. This is consistent with the findings of research which found that financial support has a positive and significant effect on entrepreneurial self-efficacy (Khaw et al, 2021;Lang & Liu, 2022;Shi et al, 2020;Sidratulmunthah et al, 2018). Based on the existing background, the purpose of this study is to examine and explain the role of entrepreneurial self-efficacy in mediating the effect of entrepreneurship education and financial support on student entrepreneurial behavior of higher education student in Bali.…”
Section: Introductionsupporting
confidence: 85%